Evaluate the Effect of Prostaglandin E2 Synthesis of Bees’ honey in Animal model - Weerakoon, W.A.S.S.; Perera, P.K.; Gunasekera, D.; Suresh, T.S. (Faculty of Indigenous Medicine, University of Colombo, 2018)
Bees' Honey (BH) has been given a valued place in traditional medicine for centuries. The usage of bee's honey as a medicine is referred to in most ancient Ayurveda medical records. The aim of this study was to evaluate the ...
Keywords: Prostaglandin E2; Bees’ honey; Arrthritis